Study of bio-mimicry surfaces for optimization of coupling performance in wheelchair racing gloves - Usma, C.; Volk, N.; Elderfield, D.; Collins, P. K. (Proceedings, 2018)
In wheelchair racing, the optimal pair of gloves, as well as knowledge of conditioning of glove-rim contact surfaces can have a significant impact on race performance. Extreme temperatures, humidity, wet or dry conditions can considerably influence not only the hand-rim friction coupling (effectiveness of the athlete`s push cycle) but also the risk of injuries, blisters or sore areas which in turn, can influence the endurance of the athlete across long distance events. This paper reports an experimental study of the effect of bio-mimicry surface textures as a supplement for heightening glove-rim coupling for dry and wet weather conditions. The paper also provides recommendations for the practical implementation of the study findings through a proposal for the design and development of a pair of bespoke gloves for a wheelchair racing athlete for initial prototyping and performance trials.